Corrosion behavior of dissimilar Al–Mg–Si alloys joint welded under hybrid CMT-laser oscillation welding - J.R. Li; J.M. Yu; L. Wang; Z. Zhang; X.N. Wang; H. Nagaumi (Journal of Materials Research and Technology)
As the corrosion behavior of 6xxx series aluminum alloys depends on composition and microstructure, the microstructure and corrosion behavior of 6082 and a new 6xxx aluminum alloy weld joint are investigated under a standard corrosion test in this study. These results show the asymmetrical welding joint structure and a distribution of corrosion severity across the weld joint. Substantial differences were observed in the size and distribution of Mg2Si particles and Fe-bearing intermetallics in various regions of the weld joint. It was found that the equiaxed grain zone on new 6xxx aluminum side is not most susceptible to corrosion, contrary to previous results, but the narrow partially melted line on 6082 side is. Not all corrosion induced by Fe-bearing intermetallics originates from the Al matrix, adjacent Fe-bearing intermetallics and Mg2Si could also form galvanic microcells, resulting in preferential dissolution of Mg2Si over the Al matrix.